Cognitive dysfunction and functional magnetic resonance imaging in systemic lupus erythematosus. (October 2015) - Barraclough, M; Elliott, R; McKie, S; Parker, B; Bruce, IN
Cognitive dysfunction is a common aspect of systemic lupus erythematosus (SLE) and is increasingly reported as a problem by patients. In many cases the exact cause is unclear. Limited correlations between specific autoantibodies or structural brain abnormalities and cognitive dysfunction in SLE have been reported. It may be that the most appropriate biomarkers have yet to be found. Functional magnetic resonance imaging (fMRI) is a technique used in many other conditions and provides sensitive measures of brain functionality during cognitive tasks. It is now beginning to be employed in SLE studies. These studies have shown that patients with SLE often perform similarly to healthy controls in terms of behavioural measures on cognitive tasks. However, SLE patients appear to employ compensatory brain mechanisms, such as increased response in fronto-parietal regions, to maintain adequate cognitive performance. As there have been only a few studies using fMRI in SLE to investigate cognitive dysfunction, many questions remain unanswered. Further research could, however, help to identify biomarkers for cognitive dysfunction in SLE.